2018
DOI: 10.1111/bju.14128
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and toxicities in patients with intermediate‐risk prostate cancer treated with brachytherapy alone or brachytherapy and supplemental external beam radiation therapy

Abstract: Brachytherapy monotherapy results in equal biochemical and distant control in both patients with one and more than one intermediate-risk features. While no significant benefit was shown, we believe that the addition of EBRT may prevent recurrence in patients with multiple intermediate-risk features and should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Apart from cervical cancer, major indications for brachytherapy are endometrial, prostate, and breast cancer (Table ). For these tumor sites, the level of evidence for brachytherapy has come from randomized controlled studies focusing not only on local control but also including OS and QOL analysis (Table ) …”
Section: Brachytherapy In the Global Oncological Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Apart from cervical cancer, major indications for brachytherapy are endometrial, prostate, and breast cancer (Table ). For these tumor sites, the level of evidence for brachytherapy has come from randomized controlled studies focusing not only on local control but also including OS and QOL analysis (Table ) …”
Section: Brachytherapy In the Global Oncological Landscapementioning
confidence: 99%
“…In fact, there is a large amount of evidence that increasing the dose to the prostate is associated with an improvement in biochemical progression‐free survival in PCa . On the basis of accumulating evidence from nonrandomized studies and from one single randomized comparison that included a few patients, permanent seed brachytherapy as monotherapy is equivalent to radical prostatectomy in patients who have low‐risk PCa, with less urinary incontinence and/or erectile dysfunction in the short term . A feasibility study has shown that recruitment to surgery versus brachytherapy is not feasible using 2‐step randomization, illustrating the difficulty of comparing both strategies .…”
Section: Brachytherapy In the Global Oncological Landscapementioning
confidence: 99%
“…Whilst many men may notice a deterioration in urinary symptoms immediately following BT, the majority have returned to baseline within 12 months with a change in IPSS score of just 1–2 points. 9,28 Some evidence suggests that more modern techniques such as 4D BT may result in a more rapid and complete resolution of symptoms.…”
Section: Early Toxicity and Post-operative Care In The First Yearmentioning
confidence: 99%
“…Urinary retention rates vary widely from 7–34% of cases. 2830 As prostate size and initial symptom scores are predictors of retention, with appropriate patient selection, the risk of acute urinary retention can be reduced. 10 Whilst acute retention can be managed with urethral catheterisation, the duration should be minimised to reduce infection risk.…”
Section: Early Toxicity and Post-operative Care In The First Yearmentioning
confidence: 99%
See 1 more Smart Citation